Role of Nurses in Public Health Education Programs on Glycaemic Control Among Type 2 Diabetic Patients in Urban and Rural Settings - Perveen, Sajida; Shehzadi, Sundas; Kanwal, Shamsa; Ashraf, Saima (Biological and Clinical Sciences Research Journal, 2025)
Type 2 diabetes mellitus (T2DM) poses a significant public health burden in Pakistan, with urban and rural populations facing distinct challenges in management. Nurse-led education programs have shown potential in improving glycaemic control and self-care behaviors, but comparative evidence between these settings remains limited. Objective: To evaluate the effectiveness of structured nurse-led public health education programs on glycaemic control and lifestyle adherence among T2DM patients in urban and rural Pakistan. Methods: A quasi-experimental study was conducted from July to December at a tertiary care hospital in Pakistan, enrolling 99 patients with type 2 diabetes mellitus (T2DM) (54 urban, 45 rural) aged 35–70 years with HbA1c levels of≥7.5%. The intervention consisted of six months of structured, nurse-led education on dietary modification, physical activity, medication adherence, and self-monitoring of blood glucose levels. HbA1c and fasting blood glucose (FBG) were measured at baseline and after six months using standardized methods. Lifestyle adherence was assessed using validated questionnaires. Data were analyzed using paired and independent t-tests as well as chi-square tests, with p < 0.05 considered statistically significant. Results: Both urban and rural groups showed significant reductions in HbA1c (urban: 9.4% to 7.8%; rural: 9.8% to 8.3%), with a greater improvement in the urban group (p = 0.04). FBG decreased significantly in both groups, with a more pronounced reduction in urban participants (p = 0.03). Lifestyle adherence improved in both settings, with significant differences in regular self-monitoring of blood glucose favoring the urban group (68.5% vs. 48.9%, p = 0.04). Conclusion: Nurse-led education significantly improves glycemic control and lifestyle adherence in patients with type 2 diabetes mellitus (T2DM) in both urban and rural settings. Urban patients experienced greater benefits, underscoring the need for tailored strategies to overcome rural healthcare barriers. Integrating such programs into national diabetes management plans could enhance long-term outcomes.